Factors affecting user satisfaction on e-services in Perpustakaan Tengku Anis / Nurfatihah S Baharuddin - S Baharuddin, Nurfatihah (2014)
The innovation of Information Communication and Technology (ICT) has changed the library management trend. The purpose of the study was to determine the factor affecting e-service satisfaction and to determine user acceptance of e-service in Perpustakaan Tengku Anis (PTA), University Technology MARA (UiTM) Cawangan Kelantan. Undergraduate students from faculty of management and business cluster are chosen as research population and it enrolled separated faculty consists of Faculty of Information Management, Faculty of Business Management, and Faculty of Accountancy. The study show that web design, navigation, usability, usefulness, information quality and responsiveness does contribute towards e-service satisfaction.